Community Development Toolkit : Volume 2. Background Volume - World Bank (Washington, DC, 2014)
The Pioneering New Approaches in Support of Sustainable Development in the Extractive Sector project promotes mine development and operation and improves opportunities for the sustainable development of mining communities and regions during all phases of the mining cycle. In part, the project responds to recommendations in "Breaking New Ground," the report of the Mining, Minerals, and Sustainable Development (MMSD) project (2002), for new approaches to enable governments, industry, and communities to create country-specific frameworks, including community sustainable development plans, that would ultimately reduce conflict, promote cooperation, and enhance the contribution of mineral-related investment to sustainable development. The result is this Community Development Toolkit, which has two main parts: 1) 17 Tools intended for use throughout the project cycle and which cover the assessment, planning, management, and evaluation phases of community development as well as stakeholder relationships; and 2) the Background volume, which contains the background and context to the project as well as an examination of the mineral policies and mining laws necessary for mineral activity to contribute to sustainable development.